1997
DOI: 10.1111/j.1600-0897.1997.tb00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Down‐Regulates LPS‐Induced Cytokine Production and NFkB Activation in Murine Macrophages

Abstract: Because cytokines are important mediators of immune function, the alteration of cytokine production by 17 beta-estradiol may thus have a profound effect on the outcome of immune response during inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
138
1
4

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(158 citation statements)
references
References 52 publications
12
138
1
4
Order By: Relevance
“…As mentioned above, exposure of macrophages in vitro to estrogen causes an increase in production of TNF-α and IL-1β [116,117]. Expression of other cytokines, like IL-6, are more dose-dependent in that proestrus levels of estrogen inhibit IL-6, whereas pregnancy levels of estrogen increases expression of IL-6 [30,118,119]. Cytokine regulation, by steroid hormones, including estrogen, occurs in two major fashions based on the presence of estrogen response elements (ERE) in the promoter region of the gene.…”
Section: Mechanisms Sectionmentioning
confidence: 96%
See 2 more Smart Citations
“…As mentioned above, exposure of macrophages in vitro to estrogen causes an increase in production of TNF-α and IL-1β [116,117]. Expression of other cytokines, like IL-6, are more dose-dependent in that proestrus levels of estrogen inhibit IL-6, whereas pregnancy levels of estrogen increases expression of IL-6 [30,118,119]. Cytokine regulation, by steroid hormones, including estrogen, occurs in two major fashions based on the presence of estrogen response elements (ERE) in the promoter region of the gene.…”
Section: Mechanisms Sectionmentioning
confidence: 96%
“…This regulation by estrogen is demonstrated by the dramatic increase in expression of IFN-γ mRNA following stimulation of cells with estrogen [120]. All other cytokines, such as IL-6, lack an ERE [121,122], but can be tightly regulated by estrogen [119]. IL-6 expression is regulated indirectly through the binding of estrogen to its receptor.…”
Section: Mechanisms Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The potential effect of estrogen in resolving HC remains unclear, but there is some evidence that estrogen has a profound effect on the cellular and cytokine immune response during inflammation. 27 Some authors reported that estradiol enhances the healing of tissue damaged by trauma. 28,29 It is known that estradiol promotes endothelial cell activities.…”
Section: Discussionmentioning
confidence: 99%
“…In murine splenic macrophages, 17β-oestradiol down-regulates the LPS-induced production of IL-1α, IL-6 and TNF-α. However, the gene expression of IL-10, IL-12, and macrophage inflammatory protein was not affected (Deshpande et al, 1997). In our pilot study we validated real-time PCR for the quantification of immune cell response after LPS stimulation.…”
Section: Discussionmentioning
confidence: 94%